Lysine Acetylation Reshapes the Downstream Signaling Landscape of Vav1 in Lymphocytes - Sonia Rodríguez-Fdez (Cells, 2020)
Vav1 works both as a catalytic Rho GTPase activator and an adaptor molecule. These functions, which are critical for T cell development and antigenic responses, are tyrosine phosphorylation-dependent. However, it is not known whether other posttranslational modifications can contribute to the regulation of the biological activity of this protein. Here, we show that Vav1 becomes acetylated on lysine residues in a stimulation- and SH2 domain-dependent manner. Using a collection of both acetylation- and deacetylation-mimicking mutants, we show that the acetylation of four lysine residues (Lys222, Lys252, Lys587, and Lys716) leads to the downmodulation of the adaptor function of Vav1 that triggers the stimulation of the nuclear factor of activated T cells (NFAT). These sites belong to two functional subclasses according to mechanistic criteria. We have also unveiled additional acetylation sites potentially involved in either the stimulation (Lys782) or the downmodulation (Lys335, Lys374) of specific Vav1-dependent downstream responses. Collectively, these results indicate that Nε-lysine acetylation can play variegated roles in the regulation of Vav1 signaling. Unlike the case of the tyrosine phosphorylation step, this new regulatory layer is not conserved in other Vav family paralogs.